Management of drooling in children. Issue 1 (30th July 2010) - Fairhurst, C B R; Cockerill, H
Abstract : Drooling beyond the age of 4 years is neurodevelopmentally abnormal. Chronic "sialorrhoea" is seen in children with abnormal oral sensation and/or motor control and more infrequently when there is excessive production of saliva. Salivary production from the paired glands is under autonomic parasympathetic control. Management of the problem relies on multidisciplinary teams with a focus on assessment and when appropriate conservative interventions, oral motor training, dental appliances, medical and surgical treatment programs. Medically, the focus is on modifying the neuroglandular control of saliva with the use of anticholinergic agents. The article covers these areas of background, assessment and management in detail.